Advancements in Fluid Power Technology: Sustainability, Electrification, and Digitalization Proceedings of the Global Fluid Power Society PhD Symposium 2024 - Ericson, Liselott; Krus, Petter; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book contains contributions from the Global Fluid Power Society (GFPS) PhD Symposium 2024. It reflects the collaborative efforts of researchers who are dedicated to pushing the boundaries of fluid power research. The GFPS PhD symposium, established in 2016 as a biannual event, is a platform for exchanging ideas and insights related to fluid power technology, among young researchers. It serves as a focal point for the exploration of various technical topics related to fluid power, including components, systems, and applications. Fluid power technology undergoes a rapid transformation towards electrification and digitalization, requiring innovation and new technical solutions across the industry, in response to societal requirements on different aspects of sustainability. The book covers a range of topics that align with the symposium's theme: Advancements in Fluid Power Technology: Sustainability, Electrification, and Digitalization. The content encompasses a wide spectrum of subjects, including fluid power applications, control and automation, energy efficiency, electrification, and environmental sustainability. The book can be a valuable reference for researchers and professionals interested in fluid power research and allied fields.
Chapter 1: Applications of Artificial Intelligence in fluid power -- Chapter 2: Control and automation in fluid power -- Chapter 3: Hydraulics Systems -- Chapter 4: Energy efficient, electrified -- Chapter 3: Hydraulic Components -- Chapter 5: Pumps/motors, Valves -- Chapter 6: Applications for renewable Energy -- Chapter 7: Safety and Reliability -- Chapter 8: Modelling and Simulation.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Fluid mechanics; Mechanics, Applied; Electric power production; Engineering Fluid Dynamics; Engineering Mechanics; Mechanical Power Engineering